Dull disasters? : how planning ahead will make a difference - Clarke, Daniel J. (Daniel Jonathan), 1980-; Dercon, Stefan (Oxford : Oxford University Press, 2016)
In recent years, typhoons have struck the Philippines and Vanuatu; earthquakes have rocked Haiti, Pakistan, and Nepal; floods have swept through Pakistan and Mozambique; droughts have hit Ethiopia, Kenya, and Somalia; and more. All led to loss of life and loss of livelihoods, and recovery will take years. One of the likely effects of climate change is to increase the likelihood of the type of extreme weather events that seems to cause these disasters. But do extreme events have to turn into disasters with huge loss of life and suffering? 'Dull Disasters?' harnesses lessons from finance, political science, economics, psychology, and the natural sciences to show how countries and their partners can be far better prepared to deal with disasters.
This edition previously issued in print: 2016.
Specialized.
Description based on online resource; title from home page (viewed on June 7, 2016).
Keywords: Emergency management; Crisis management; Organizational resilience